Pengaruh Penggunaan Handphone Pada Siswa Sekolah Dasar - Putra, Ary Antony; Wahyuni, Ida Windi; Alucyana; Ajriyah (UIR Press, 2021)
The problem in this study is the misuse of cell phones by elementary school students, resulting in deviant student behaviour. Some cases found in the community are students' emotional uncontrolled, easily angry, indifferent, and selfish. The type of this research is quantitative research. The research sample was 180 students. The data collection techniques used were questionnaires and documentation. At the same time, the data analysis of this research uses descriptive qualitative and quantitative analysis methods. The results of this study show that there is no significant effect in the use of cellphone on the social behaviour of student at SDN 011 Simalinyang Kampar Kiri Tengah District Kampar Regency, which the following information; The value of t-test < t-tabel namely 1.933 < 2 means that Ha is rejected and Ho is accepted. The variable use of the mobile phone has a significance level of 0.057 > 0.005. The meaning is insignificant, with Ha rejected, and Ho accepted. So the conclusion is that there is no significant influence between the use of cellphones on the social behaviour of students at SDN 011 Simalinyang, Kampar Kiri Tengah District, Kampar Regency.